LMO1 Plays an Oncogenic Role in Human Glioma Associated With NF-kB Pathway - Gao, Lei; Wu, Jia; Wang, Hai; Yang, Yongyu; Zheng, Zongliao; Ni, Bowen; Wang, Xiran; Peng, Yuping; Li, Yaomin (Frontiers in Oncology, 2022)
Background: LIM domain only protein1（LMO1), a nuclear transcription coregulator, is implicated in the pathogenesis of T-cell acute lymphoblastic leukemia and neuroblastoma. However, the clinical significance and potential mechanism of LMO1 in human gliomas remain to be determined. Methods: In this study, expression level data and clinical information were obtained via three databases. The Cox proportional hazards regression model was used to predict outcomes for glioma patients. In vitro and in vivo assays were used to explore the function of LMO1 in human glioma. Gene set enrichment analysis (GSEA) , RNA-Seq and western blot were used to explore the potential molecular mechanisms. A prognostic model was built for predicting overall survival(OS) of human glioma patients. Results: High LMO1 expression was associated with a high tumor grade and a poor prognosis in patients. High levels of LMO1 mRNA were correlated with poor prognosis in patients with isocitrate dehydrogenase (IDH)-wild-type (wt) and 1p/19q non-codeletion gliomas. Gene silencing of LMO1 significantly inhibited tumor growth, invasion and migration in vitro. In contrast, LMO1 over-expression promoted tumor growth, invasion and migration. Mechanically, LMO1 may positively regulate the level of NGFR mRNA and protein. NGFR mediated the regulation between LMO1 and NF-kB activation. Consistently, the nude mice study further confirmed that knockdown of LMO1 blocked tumor growth via NGFR-NF-kB axis. Finally, The nomogram based on the LMO1 signature for overall survival (OS) prediction in human glioma patients exhibited good performance in the individual mortality risk. Conclusion: This study provides new insights and evidences that high level expression of LMO1 is significantly correlated with progression and prognosis in human gliomas. LMO1 played a critical role in tumorigenesis and progression. The present study first investigated the LMO1–NGFR–NF-kB axis regulate cell growth and invasion in human glioma cells, whereby targeting this pathway may be a therapeutic target for glioma.